Paradoxes of functional neurosurgery: clues from basal ganglia recordings. - Brown, P; Eusebio, A (2008)
Deep brain stimulation (DBS) can be remarkably effective in treating movement disorders such as Parkinson's disease, dystonia, and essential tremor. Yet these effects remain essentially unexplained, even paradoxical. Equally challenging is the fact that DBS of motor targets in the basal ganglia appears to reverse abnormalities of movement without any obvious deleterious effects on remaining aspects of movement. Here, we explore the extent to which the noisy signal hypothesis might help solve some of these apparent paradoxes. Essentially the hypothesis, first tentatively advanced by Marsden and Obeso (1994), suggests that disease leads to a pattern of basal ganglia activity that disrupts local and distant function and that surgery acts to suppress or override this noisy signal. Critical to the success this theory is that different disease phenotypes are associated with different patterns of noisy signal, and we survey the evidence to support this contention, with specific emphasis on different types of pathological synchronization. However, just as DBS may suppress or override noisy signals in the basal ganglia, it must equally antagonize any remaining physiological functioning in these key motor structures. We argue that the latter effect of DBS becomes manifest when baseline motor performance is relatively preserved, i.e., when pathological activity is limited. Under these circumstances, the deleterious effects of DBS are no longer obscured by its therapeutic actions in suppressing noisy signals. Whether true, oversimplified or simply incorrect, the noisy signal hypothesis has served to focus attention on the detailed character of basal ganglia discharge and its variation with disease and therapy.